Chronic whiplash and central sensitization; an evaluation of the role of a myofascial trigger points in pain modulation - Freeman, Michael D; Nystrom, Ake; Centeno, Christopher (Journal of Brachial Plexus and Peripheral Nerve Injury, 2009)
Objective it has been established that chronic neck pain following whiplash is associated with the phenomenon of central sensitization, in which injured and uninjured parts of the body exhibit lowered pain thresholds due to an alteration in central pain processing. it has furthermore been hypothesized that peripheral sources of nociception in the muscles may perpetuate central sensitization in chronic whiplash. the hypothesis explored in the present study was whether myofascial trigger points serve as a modulator of central sensitization in subjects with chronic neck pain.Design controlled case series.Setting outpatient chronic pain clinic.Subjects seventeen patients with chronic and intractable neck pain and 10 healthy controls without complaints of neck pain.Intervention symptomatic subjects received anesthetic infiltration of myofascial trigger points in the upper trapezius muscles and controls received the anesthetic in the thigh.Outcome measures: pre and post injection cervical range of motion, pressure pain thresholds (ppt) over the infraspinatus, wrist extensor, and tibialis anterior muscles. sensitivity to light (photophobia) and subjects’ perception of pain using a visual analog scale (vas) were also evaluated before and after injections. only the ppt was evaluated in the asymptomatic controls.Results immediate (within 1 minute) alterations in cervical range of motion and pressure pain thresholds were observed following an average of 3.8 injections with 1–2 cc of 1% lidocaine into carefully identified trigger points. cervical range of motion increased by an average of 49% (p = 0.000) in flexion and 44% (p = 0.001) in extension, 47% (p = 0.000) and 28% (p < 0.016) in right and left lateral flexion, and a 27% (p = 0.002) and 45% (p = 0.000) in right and left rotation. ppt were found increased by 68% over the infraspinatus (p = 0.000), by 78% over the wrist extensors (p = 0.000), and by 64% over the tibialis anterior (p = 0.002). among 11 subjects with photophobia, only 2 remained sensitive to light after the trigger point injections (p = 0.033). average vas dropped by 57%, from 6.1 to 2.6 (p = 0.000). no significant changes in ppt were observed in the control group following lidocaine infiltration of the thigh.Conclusion the present data suggest that myofascial trigger points serve to perpetuate lowered pain thresholds in uninjured tissues. additionally, it appears that lowered pain thresholds associated with central sensitization can be immediately reversed, even when associated with long standing chronic neck pain. although the effects resulting from anesthesia of trigger points in the present study were temporary, it is possible that surgical excision or ablation of the same trigger points may offer more permanent solutions for chronic neck pain patients. further study is needed to evaluate these and other options for such patients.